TINGKAT AWARENESS MASYARAKAT TERHADAP BENCANA TSUNAMI DI KECAMATAN CARITA, KABUPATEN PANDEGLANG BANTEN - Meassa Monikha Sari (UNIVERSITAS NEGERI MAKASSAR, 2022)
The tsunami on Carita Coast caused considerable losses, damages, and casualties. The casualties can be caused by the unpreparedness of the community in dealing with tsunami. This study aims are to determine the level of community awareness to overcome the tsunami in Carita District, Pandeglang. Data was collected by spreading questionnaires to 158 respondents and then analyzing by validity test, reliability test and descriptive analysis. The result shown that the level of community awareness of tsunami disaster in Carita (Case Study of Sukarame Village, Sukajadi Village, Carita Village, Banjarmasin Village and Pejamben Village) was 14% of the total respondents are low awareness, then there are 35% of people have moderate awareness level, and 51% have an elevated level of awareness of the tsunami disaster. Overall, the level of community awareness in dealing with tsunami is included in the sufficient category. The community awareness has increased significantly after experiencing the tsunami in 2018 compared to before the disaster. The socialization was still needed to improve community preparedness behaviors in overcoming the tsunami.